DALANG YANG BERJEJARING (Studi Kasus Enthus Susmono Pada Pemilihan Kepala Daerah Kabupaten Tegal Tahun 2013) - Puspa Fitri Anggraeni; Fitriyah . (Journal of Politic and Government Studies, 2019)
This discusses a puppeteer being a regent using his network, the puppeteer Enthus or commonly called Ki Enthus utilizing his social network to win the 2013 regional head elections in Tegal Regency, Central Java. the title selection was in the background because there was an interesting phenomenon that occurred in the Tegal regional election, namely Ki Enthus, a puppeteer who did not have a political background, but he ventured to advance to become the regent of Tegal Regency in 2013, because he wanted to realize that Tegal must have leaders who are clean and effective in serving the community. This study aims to see the condition of Enthus Susmono social network in winning in the regional head elections in Tegal Regency in 2013. The type of research that researchers use is descriptive qualitative with a case study method. Data collection techniques through primary data in the form of interviews and secondary data in the form of documents related to research. The informants chosen in this study were the closest people or the belief of the late Enthus Susmono, Deputy Regent of Tegal in 2013, bearer political parties, Success Teams and Community Leaders.Ki Enthus Susmono victory in the regional head election in Tegal Regency in 2013 was not only based on Ki Enthus popularity, but from his Deputy contribution, Umi Azizah. The Enthus-Umi couple has its own social network, and in their campaigns they share their respective duties. Umi Azizah has a strong base in the eyes of the public, especially mothers. This is because Umi Azizah has been the Chair 2 of Fatayat and Muslimat for two periods. The success of Ki Enthus in winning the regional head elections in Tegal Regency in 2013 was inseparable from several factors in the eyes of the people of Tegal Regency, through puppet shows and the style of mastering it was different. Ki Enthus strategy proves his ability in the art world, while the strategy carried out by Umi Azizah can create songs as a medium of communication to the public. The winning strategy carried out by the pair Ki Enthus and Umi Azizah, more utilizing traditional media.Keywords : Mastermind, Popularity, Victory, Sosial Capital, Networking, Regional Election